Communication Strategy of Importance of Vaccination using Social Media and Public Relations - Nurlaela, Neneng; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
The purpose of this study is to build the value of public health in Indonesia about the importance of vaccination using social media strategy and public relations through the integrated social media strategy which lead to be the hub for all BFM’s corporate communication processes which related to vaccination towards all the stakeholders through the proactive, conversational and participative approach ; Develop the social media program in order to raise the corporate image of  BFM by leveraging the great performance and achievement of the company within vaccination ; Build the system of communication model for sustainability impelementation. The methodology of this research was qualitative method, the surveyed with the direct research, interviews and research study towards the routine communication activities. Interviews were conducted in order to check the main issue to implement the integrated communication system and also building the communication model. The result of this research confirmed that the existing communication problems  are law awareness and negative perception about vaccine. Some of the implication practices gave the specific recommendation, such as the integrated social media through the content management which combined with public relations activities.  Key Words: Vaccine, Social Media, Value, Public Health, Situation in BFM